Birth weight, umbilical and placental traits in relation to neonatal loss in cloned pigs. (September 2017) - Ao, Zheng; Liu, Dewu; Zhao, Chengfa; Yue, Zhimin; Shi, Junsong; Zhou, Rong; Cai, Gengyuan; Zheng, Enqin; Li, Zicong; Wu, Zhenfang
Abstract: Cloned piglets generated through somatic cell nuclear transfer (SCNT) have a high rate of neonatal death. Postnatal loss is associated with low birth weight, umbilical status and placental parameters in fertilisation-derived piglets. To investigate whether or not this relationship also exists in cloned piglets, birth weight, umbilical status, placental parameters, placental morphology and gene expression pattern were compared among four piglet groups, namely, SCNT-derived male piglets that died within 4 days (SCNT-DW4), SCNT-derived male piglets that survived over 4 days (SCNT-SO4), artificial insemination (AI)-generated male piglets that died within 4 days (AI-DW4) and AI-generated male piglets that survived over 4 days (AI-SO4). Results showed that the occurring frequency of abnormal umbilical cord in SCNT-DW4 piglets was significantly higher than that in AI-SO4 piglets but was similar to that in SCNT-SO4 and AI-DW4 piglets. The birth weight, placental surface area and placental weight of AI-SO4, AI-DW4 and SCNT-SO4 groups were similar but were significantly higher than those in SCNT-DW4 group. SCNT-SO4 placentas exhibited mild but SCNT-DW4 placentas showed severe morphological abnormalities compared with AI-SO4 placentas. The expression profiles of imprinting, angiopoiesis, nutrient transport, apoptosis and oxidative stress-related genes in SCNT-DW4 placentas were erroneous compared with those in SCNT-SO4 and AI-SO4 placentas, which both had similar gene expression patterns. These results indicate that birth weight, umbilical status, placental parameters, placental morphology and gene expression were associated with neonatal death of cloned piglets. The high loss of cloned piglets during neonatal age may be caused by severe deficiency of extra-embryonic development during prenatal stage. Highlights: Cloned piglets have a very high mortality rate during the neonatal age. Neonatal death of cloned piglets was associated with low birth weight. Neonatal loss of cloned piglets was related to umbilical and placental traits.